Application of the Inverse Almost Ideal Demand System to Welfare Analysis - Frank Jensen; Max Nielsen; Eva Roth (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
This paper presents the theoretical properties of the Inverse Almost Ideal De-mand System and applies the system on time series data for cod, herring and plaice in Denmark (1986 to 2001). Furthermore, the shortcoming of the Inverse Almost Ideal Demand System when applied to welfare analysis is discussed. The properties of the demand system show that - since the demand system is a second-order approximation to the true system - it does not have global appli-cability for welfare measurement. It may, therefore, not satisfy the conditions for calculation of consumer surplus (negative slope and positive point of inter-section with the price-axis). The theoretical point is illustrated by an empirical example of the Danish fish market. Using a vector auto regressive model in er-ror correction form to overcome the problem of non-stationarity of data, the In-verse Almost Ideal Demand System is estimated. For cod the intercept is nega-tive and for herring and plaice the slope of the demand function is positive in the data interval investigated. Thus, the estimated demand system is not suitable for welfare analysis.
Keywords: 330; Inverse Almost Ideal Demand System; Welfare analysis; Co-integration and Fish; Wohlfahrtsanalyse; Nachfragesystem; Fischmarkt; Kointegration